Bariatric-induced microbiome changes alter MASLD development in association with changes in the innate immune system - Shera, Simer; Katzka, William; Yang, Julianne C.; Chang, Candace; Arias-Jayo, Nerea; Lagishetty, Venu; Balioukova, Anna; Chen, Yijun; Dutson, Erik; Li, Zhaoping; Mayer, Emeran A.; Pisegna, Joseph R.; et al. (Frontiers in Microbiology, 2024)
Introduction: Metabolic dysfunction-associated steatotic liver disease (MASLD) affects nearly 25% of the population and is the leading cause for liver-related mortality. Bariatric surgery is a wellknown treatment for MASLD and obesity. Understanding the fundamental mechanisms by which bariatric surgery can alter MASLD can lead to new avenues of therapy and research. Previous studies have identified the microbiome's role in bariatric surgery and in inflammatory immune cell populations. The host innate immune system modulates hepatic inflammation and fibrosis, and thus the progression of MASLD. The precise role of immune cell types in the pathogenesis of MASLD remains an active area of investigation. The aim of this study was to understand the interplay between microbiota composition post-bariatric surgery and the immune system in MASLD. Methods: Eighteen morbidly obese females undergoing sleeve gastrectomy were followed pre-and post-surgery. Stool from four patients, showing resolved MASLD post-surgery with sustained weight loss, was transplanted into antibiotic treated mice. Mice received pre-or post-surgery stool and were fed a standard or high-fat diet. Bodyweight, food intake, and physiological parameters were tracked weekly. Metabolic parameters were measured post-study termination. Results: The human study revealed that bariatric surgery led to significant weight loss (p>0.05), decreased inflammatory markers, and improved glucose levels six months post-surgery. Patients with weight loss of 20% or more showed distinct changes in blood metabolites and gut microbiome composition, notably an increase in Bacteroides. The mouse model confirmed surgery-induced microbiome changes to be a major factor in the reduction of markers and attenuation of MASLD progression. Mice receiving post-surgery fecal transplants had significantly less weight gain and liver steatosis compared to pre-surgery recipients. There was also a significant decrease in inflammatory cytokines interferon gamma, interleukin 2, interleukin 15, and mig. This was accompanied by alterations in liver immunophenotype, including an increase in natural killer T cells and reduction of Kupfer cells in the post-surgery transplant group Discussion: Our findings suggest surgery induced microbial changes significantly reduce inflammatory markers and fatty liver progression. The results indicate a potential causal link between the microbiome and the host immune system, possibly mediated through modulation of liver NKT and Kupffer cells.